REFORMASI HUKUM DAN POSISI PERADILAN AGAMA DI INDONESIA - JAENAL ARIPIN (Al Qalam, 2009)
The Religious Court has changed in the way of the law paradigm change applied in Indonesia by applying the concept of separation of power, not distribution of power. Its status and position as the administrator of judicial power, has the independency at the moment because it is not under the executive power any longer. Its competence, has also changed with new competencies: syari'ah economy, the enactment of ancestry and adoption, and of hisab and rukyah. But the material law is not changed in either old or new competency. Because there is no change in law material, the judges perform not only as the law administrator but also as the law interpreter/ rechstvinding on law in book, law in concretto, and/or living law like in legal culture. This is meant that justice seekers will ftel the pure justice.